Mitochondrial mutations and mitoepigenetics: Focus on regulation of oxidative stress-induced responses in breast cancers. (August 2022) - Chen, Kuo; Lu, Pengwei; Beeraka, Narasimha M.; Sukocheva, Olga A.; Madhunapantula, SubbaRao V.; Liu, Junqi; Sinelnikov, Mikhail Y.; Nikolenko, Vladimir N.; Bulygin, Kirill V.; Mikhaleva, Liudmila M.; Reshetov, Igor V.; Gu, Yuanting; et al.
Highlights: Epigenetic regulation of mitochondrial DNA (mtDNA) (mitoepigenetics) is an emerging and fast developing field of research. Cancer cells contain oxidative stress-mediated defects in mtDNA repair system, nucleoid-based organization, and mitoepigenetic regulation. Dysbalanced mitoepigenetics and adverse regulation of oxidative phosphorylation (OXPHOS) can efficiently facilitate cancer cell survival. Anti-cancer effects of several mitochondria-targeting agents warrant further testing in breast cancers. Crosstalk mechanism between mitoepigenetics and cancer-associated mtDNA mutations is a promising therapy target in breast cancers. Abstract: Epigenetic regulation of mitochondrial DNA (mtDNA) is an emerging and fast-developing field of research. Compared to regulation of nucler DNA, mechanisms of mtDNA epigenetic regulation (mitoepigenetics) remain less investigated. However, mitochondrial signaling directs various vital intracellular processes including aerobic respiration, apoptosis, cell proliferation and survival, nucleic acid synthesis, and oxidative stress. The later process and associated mismanagement of reactive oxygen species (ROS) cascade were associated with cancer progression. It has been demonstrated that cancer cells contain ROS/oxidative stress-mediated defects in mtDNA repair system and mitochondrial nucleoid protection. Furthermore, mtDNA is vulnerable to damage caused by somatic mutations, resulting in the dysfunction of the mitochondrial respiratory chain and energy production, which fosters further generation of ROS and promotes oncogenicity. Mitochondrial proteins are encoded by the collective mitochondrial genome that comprises both nuclear and mitochondrial genomes coupled by crosstalk. Recent reports determined the defects in the collective mitochondrial genome that are conducive to breast cancer initiation and progression. Mutational damage to mtDNA, as well as its overproliferation and deletions, were reported to alter the nuclear epigenetic landscape. Unbalanced mitoepigenetics and adverse regulation of oxidative phosphorylation (OXPHOS) can efficiently facilitate cancer cell survival. Accordingly, several mitochondria-targeting therapeutic agents (biguanides, OXPHOS inhibitors, vitamin-E analogues, and antibiotic bedaquiline) were suggested for future clinical trials in breast cancer patients. However, crosstalk mechanisms between altered mitoepigenetics and cancer-associated mtDNA mutations remain largely unclear. Hence, mtDNA mutations and epigenetic modifications could be considered as potential molecular markers for early diagnosis and targeted therapy of breast cancer. This review discusses the role of mitoepigenetic regulation in cancer cells and potential employment of mtDNA modifications as novel anti-cancer targets.